Meta-Analysis of the Effect of Telemonitoring on Blood Sugar Levels and Quality of Life in Diabetes Patients - Sholihah, Anisa Asri; Tamtomo, Didik Gunawan; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Type 2 diabetes mellitus (DM), a chronic disease, requires continuous monitoring and treatment to have a better quality of life. Telemonitoring is a medium that may help in monitoring patients with type 2 DM. This study aimed to analyze the effect of using telemonitoring on blood sugar levels and quality of life of patients with type 2 DM with a meta-analysis study.Subjects and Method: This was a systematic review and meta-analysis conducted with PRISMA flow diagram. The articles were collected through journal databases, including PubMed, Google Scholar, Science Direct, and ProQuest, published in 2000-2021. The keywords used were ("telemedicine" OR "tele-monitoring" OR "tele-monitoring") AND ("diabetes" OR "diabetes mellitus" OR "diabetes mellitus type 2") AND ("glucose level") AND ("quality of life"). The searching of articles used the PICO model. Population: people with type 2 diabetes mellitus, Intervention: telemonitoring, Comparison: not using telemonitoring, Outcome: blood sugar level and quality of life. Inclusion criteria were full-text articles with Randomized Controlled Trial (RCT) study design, published in English, with the effect measure of Mean SD. Eligible articles were analyzed using Revman 5.3.Results: A meta-analysis of 11 primary studies on the use of telemonitoring of blood sugar level showed a decrease in blood sugar (HbA1c) levels in patients with type 2 diabetes by 0.20 times compared to not using telemonitoring (SMD= -0.20; 95% CI= -0.39 to -0.01; p= 0.040). A meta-analysis of 6 primary studies on the use of telemonitoring on quality of life showed an increase in quality of life in type 2 diabetes patients by 0.16 times compared to not using telemonitoring (SMD= -0.16; 95% CI= -0.29 to -0.03; p= 0.020).Conclusion: Telemonitoring can improve blood sugar levels and the quality of life of patients with type 2 diabetes.Keywords: telemonitoring, type 2 diabetes mellitus, quality of life, meta-analysisCorrespondence: Anisa Asri Sholihah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: anisaasri92@gmail.com. Mobile: 085740972908.Indonesian Journal of Medicine (2021), 06(03): 246-257https://doi.org/10.26911/theijmed.2021.06.03.02